Slow Looking at Artworks in the Museum Context—Exploration of the Viewers’ Observations with Reflexive Thematic Analysis - Timonen, Kristina (Cultural Arts Research and Development, 2025)
Art can serve as a contextual element and promote wellbeing. Meanings derived from artworks are related to, for instance, cultural backgrounds, languages, mood and viewing technique. This study focused on art viewers’ experiences, and the participants were picked with different cultural backgrounds, mood settings and spoken languages in mind. The study was conducted with the Western Finland health care services and executed at the Kuntsi Museum of Modern Art in Vaasa. Nine volunteers contributed to the study by slowly viewing artworks alone or with a companion, taking 5–10 minutes each work, photographing them, writing down thoughts, or discussing them on an audio recorder. Three people visited 4–6 exhibitions, while the rest visited one. Participation was unrelated to anyone’s studies, work, healthcare or other arrangements. The data was analysed with reflexive thematic analysis, and its suitability as a method was also tested to uncover people’s thoughts during the slow looking experience. Results show that viewers make individual connections with artworks that touch upon their interests. Viewing artworks also helps individuals to discover novel ideas on various topics. Viewer’s background and personal conditions, such as mood, language, culture, affect interest and the ability to notice details in artworks. Understandably, language has a role in how people organise their thoughts and create a platform for creative cognition. Spending time with artworks can have a positive effect, especially on mood; thus, art can counterbalance the fast-paced lifestyles and contemporary anxieties of people in the 21st century, leading to possibilities for better wellbeing.